Menilai Tingkat Religiusitas dan Pengetahuan pada Perilaku Beli Generasi Muda Terhadap Produk Pangan Halal - Purnasari, NUrwulan; Hasyim, Fuad; Sabarisman, Iman (Universitas Islam Negeri Sunan Kudus, 2018)
Halal food products are a necessity for a Muslim. However, not all food circulating in the market is halal products, so people must be smart in choosing food products. This study aims to determine the relationship between knowledge and the level of religiosity of young people towards the decision to buy halal food products. Based on the sample of young people from various universities in the Yogyakarta and Surakarta areas the results showed that the level of religiosity and knowledge about halal food products had an influence on purchasing decisions for halal products, except that the level of religiosity had a higher influence. This shows that the level of religiosity is an important factor that needs to be considered especially in promoting halal food products.